DIGITALIZATION STRATEGIES THROUGH BRAND IMAGE, CELEBRITY ENDORSER, AND EWOM OF INDONESIAN HALAL PRODUCT TOWARDS A PURCHASE DECISION - Yusepaldo Pasharibu; Ajeng Nurhidayah (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
A purchase decision is one essential goal that all businesses want to achieve, particularly to sustain their business. In order to pursue that objective, businesses apply various digitalization strategies, including strengthening the image of their brands, approaching celebrity endorsers, and spreading the power of electronics word of mouth (eWOM). However, there was an inconsistent result that stated brand image and eWOM do not influence a purchase decision. Based on those explanations, this study examined whether brand image, celebrity endorser and eWOM have an influence towards purchase decision. To aim the research objectives, the data from 245 respondents collected using a purposive sampling technique through both online and offline questionnaires. Thus, collected data were analyzed using multiple regression analysis techniques. The results of this study conclude that all variables, including brand image, celebrity endorser, and eWOM positively influence towards purchase decision of Indonesian halal products both partially and simultaneously. Furthermore, the degree of the significant result might allegedly be supported by some predominate indicators, including the research object that recognizes as a halal product or responsible and trustee. Keywords: brand image, celebrity endorser, electronic word of mouth, purchase decision